Analysis of Nanobubble-oxygenated Water for Horticultural Applications - Eric J. DeBoer; Michael D. Richardson; Thanos Gentimis; John H. McCalla (HortTechnology)
The theoretical properties of nanobubbles (NBs), such as a negative surface charge and large interfacial surface area, allow for highly efficient gas transfer and stagnation time in water and may reduce the surface tension of NB-treated water sources. These properties make NBs unique candidates for addressing issues like root zone oxygen deficiency, common in conventional and hydroponic crop production. Therefore, the objectives of this research were to confirm the presence of NBs in treated water and determine how time and temperature affect dissolved oxygen (DO) retention in NB-oxygenated water. Two membrane-based NB injection systems were compared with a standard method of aeration (aquarium air stone) and untreated potable water to determine the effect of NB oxygenation on DO retention time and nanoscopic particle size and concentration of potable water sources. NB oxygenation of potable water generally resulted in a greater number of nanoparticles detected compared with untreated potable water. NB oxygenation increased initial levels of DO in potable water when compared with the standard air stone. NB oxygenation failed to increase DO retention time compared with a standard air stone, regardless of water temperature. NB oxygenation remains a method of efficiently oxygenating large volumes of water, although the NBs investigated in the study did not increase DO retention in a potable water source.